Pertanggungjawaban Pidana bagi Pelaku Tindak Pidana Pencemaran dan Perusakan Lingkungan Hidup (Studi Putusan Nomor: 464/PID.B/LH/2022/PN.MTR) - Qushaery, Ahmad; Maswandi, Maswandi; Fithri, Beby Suryani (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to Analyze the Law and Criminal Liability for Environmental Pollution Due to Waste Dumping, as well as analyze the Legal Liability in Decision 464/PID. B/LH/2022/PN. MTR. This study uses a normative juridical approach to analyze the application of law and criminal liability in cases of environmental pollution due to waste dumping, based on Decision Number 464/PID. B/LH/2022/PN. MTR. The data was analyzed qualitatively from legal documents, interviews, and literature. The results of the study show that environmental pollution due to B3 waste dumping is a serious violation with a wide impact on the ecosystem and the quality of life of the community. The UUPPLH provides a legal framework to deal with these violations through criminal and administrative sanctions. Decision Number 464/PID. B/LH/2022/PN. MTR shows the strict application of environmental criminal law by imposing sanctions on the perpetrator, Heri Irawan, to provide a deterrent effect. Although effective, strengthening supervision, business compliance, and community involvement are still needed. This collaboration is important to create a sustainable and pollution-free environment.